Potency Microbial Unicellular Filoplan Chili and Its Inhibitory to Collectotrichum capsici Causal Antraknose Disease on Chili (Capsicum annuum L.) - Tanzil, Ahmad Ilham; Djauhari, Syamsuddin; Sulistyowati, Liliek (Jurnal Online Pertanian Tropik, 2020)
This study was conducted to isolate filoplan unicellular microbes which have antibiosis ability and characterize the secondary metabolite produced to inhibit Collectotrichum capsici in-vitro. This research was conducted at the Departement Plant Pest and Diseases, University of Brawijaya. Microbe isolated from the surface of chilies in a different age. Isolates microbes were tested for antagonistic potential against C. capsici. The persistence of the potential antagonist under different conditions of pH, temperature, and the light was also examined. An antagonist test was conducted to confirm the antibiosis mechanism. Furthermore, extracts were characterized using pH, light exposure, and temperature. The most potential antagonist was identified as isolate C3C with 36.20% inhibition. pH 5, 350C temperature, and light exposure of 0% is the best media optimization with the percentage of inhibition 37.5%, 38.2%, and 42.3%.